The production of carbon nanotubes using two-stage chemical vapor deposition and their potential use in protein purification - Mujawar, Mubarak; Yusof, F.; Alkhatib, M. (Elsevier BV, 2011)
Carbon nanotubes (CNTs) were produced by gas phase two-stage chemical vapor deposition using ferrocene as a catalyst and acetylene (C 2 H 2 ) and hydrogen (H 2 ) as precursor gases. The CNTs were characterized using field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), and by thermogravimetric analysis (TGA). Process parameters such as reaction temperature, reaction time and gas flow rates of C 2 H 2 and H 2 were optimized using Design-Expert software v.6.0.8. The statistical analysis reveals that the optimum conditions for the CNT production were reaction temperature of 850°C, reaction time of 60min and gases flow rates of 40 and 150ml/min for C 2 H 2 and H 2 , respectively. The optimum CNTs prepared were purified and functionalized using acid treatment. Both functionalized and nonfunctionalized CNTs were used as column chromatographic media for skim latex protein purification. Skim latex protein was used as the model protein for the recovery of useful proteins and enzymes. During purification, process parameters such as pH and ionic strength of the running buffer were optimized to enhance protein purification. Results revealed that CNTs behave efficiently as a hydrophobic interaction chromatographic (HIC) media.